Positron Emission Tomography and Granulosa Cell Tumor Recurrence: A Report of 2 Cases. Issue 9 (1st November 2009) - Raj, Ganendra; Proietto, Anthony; Jaaback, Kenneth
Abstract : Two case reports of women with recurrent granulosa cell tumors identified initially by increasing levels of inhibin. As part of their investigation to assess the extent of the recurrence, an abdominopelvic computed tomography and a positron emission tomography scans were performed. Interestingly, the recurrent tumors were identified on the abdominopelvic computed tomography but not on the positron emission tomography scan. These recurrences were confirmed at surgery, and the histopathologic findings were identical to the original lesion.